PENGARUH KUALITAS PELAYANAN TERHADAP LOYALITAS PASIEN RAWAT JALAN RUMAH SAKIT LUDIRA HUSADA TAMA YOGYAKARTA: - - Y.B. Arya Primantana; Rini Dwiastuti (Jurnal Farmasi & Sains Indonesia, 2025)
This study analyzes the effect of service quality on outpatient loyalty through patient satisfaction at RS Ludira Husada Tama Yogyakarta. Using purposive sampling, 150 outpatients completed SERVQUAL-based questionnaires analyzed with SEM-PLS. Results showed that tangible (p=0.017) and assurance (p=0.002) dimensions significantly influenced patient satisfaction, while reliability (p=0.554), responsiveness (p=0.646), and empathy (p=0.902) did not. Patient satisfaction significantly influenced loyalty (p=0.001). The findings indicate that physical facilities and service assurance are critical factors in building patient loyalty through satisfaction in outpatient settings.. Keywords: service quality, patient satisfaction, patient loyalty, outpatient, SERVQUAL